Strategic Leadership Practices in Fostering Innovation Culture in Vocational Education: A Case Study - Sari, Indah Permata; Yasmin, Wifa Rasuna; Triyoga, Rihadini; Indri, Indri; Mulawarman, Widyatmike Gede; Akhmad, Akhmad (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study explores how principals’ strategic leadership practices foster an innovation culture in vocational education and contribute to school competitiveness, using SMK 14 Samarinda as a case study. Previous studies have discussed strategic leadership and school innovation separately, yet limited research explains how leadership visions are translated into operational practices within vocational school contexts.Methods – This research employed a qualitative case study design. Data were collected through in-depth semi-structured interviews with the school principal, supported by document analysis. Thematic analysis following the Miles and Huberman interactive model was applied, involving data reduction, coding, categorization, and conclusion drawing. Credibility was strengthened through source triangulation and member checking. Findings – The findings indicate that strategic leadership at SMK 14 Samarinda promotes an innovation culture through consistent vision communication, data-driven decision-making, collaborative teacher engagement, implementation of project-based learning, and continuous academic supervision. These leadership practices function as micro-mechanisms linking strategic policies with innovative classroom practices, contributing to improved learning quality and strengthening the school’s competitiveness in vocational education. Research Implications – This study provides practical implications for vocational school leaders in implementing data-driven, adaptive, and collaborative strategic leadership to foster sustainable innovation cultures. As this study focuses on a single case school and a limited set of informants, the findings are context-specific and cannot be broadly generalized. Future research should involve comparative multi-school designs and multi-informant data sources to strengthen external validity.